Pengaruh Yoga pada Ibu Inpartu Primigravida terhadap Kemajuan Persalinan Kala I Fase Aktif - Diana Noor Fatmawati; Evi Dwi Prastiwi (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2017)
The fears, anxiety, and fear both of during pregnancy, childbirth or in the face after childbirth often experienced by primigravida. Increased maternal psychological burden can cause a variety of complications that can result in the availability and quality of maternal persalianan fetus. Yoga can help mothers to overcome anxiety when faced with the birth process. This study aims to determine the progress of labor primigravida difference between the treated yoga and yoga as well as how much yoga affect the progress of labor primigravida.The research design is the design of pre experiment design with a static group comparison approach. The population was primigravida is the active phase of the first stage from April to November 2016 in BPM Nurul Aini as many as 34 people. Total sample is 17 people doing yoga and 17 people do not do yoga. The statistical test used was Wilcoxon Mann - Whitney U - Test (SPSS) and Linear Regression Test.The results of research that labor progress Kala Active Phase I primigravida given treatment yoga almost half the normal progress ie 6 hours of 8 people (47.1%) and were not given the treatment yoga accelerating progress on the 5 o'clock as many as 1 ( 5.9%). Wilcoxon Mann Whitney U Test Results in SPSS p value <0.05, it indicates that the difference between the labor progress primigravida treated yoga exercises with yoga exercises that do not. And then to know how far the influence of yoga exercises on the progress of the first stage of labor is the active phase primigravida performed linear regression test and get the value of R2 = 0.383, which means yoga exercises influence by 38.3% against the first stage of labor progress for primiravida active phase. In an effort to overcome anxiety and pain during childbirth, yoga can be disseminated to the public to be done routinely. Their yoga classes maternal health services can facilitate pregnant women to actively follow it. The participation of health workers, cadres, families and communities in the implementation of yoga classes can help implement a yoga class for pregnant women.